Maternal, cord, and three‐year‐old child serum thyroid hormone concentrations in the Health Outcomes and Measures of the Environment study. (19th January 2020) - Doherty, Brett T.; Kosarek, Noelle; Hoofnagle, Andy N.; Xu, Yingying; Zoeller, R. Thomas; Yolton, Kimberly; Chen, Aimin; Lanphear, Bruce P.; Braun, Joseph M.; Romano, Megan E.
Abstract: Purpose: Maternal thyroid function during pregnancy may influence offspring thyroid function, though relations between maternal and child thyroid function are incompletely understood. We sought to characterize relations between maternal, cord and child thyroid hormone concentrations in a population of mother‐child pairs with largely normal thyroid function. Methods: In a prospective birth cohort, we measured thyroid hormone concentrations in 203 mothers at 16 gestational weeks, 273 newborns and 159 children at 3 years among participants in the Health Outcomes and Measures of the Environment (HOME) Study. We used multivariable linear regression to estimate associations of maternal thyroid hormones during pregnancy with cord serum thyroid hormones and also estimated associations of maternal and cord thyroid hormones with child thyroid‐stimulating hormone (TSH). Results: Each doubling of maternal TSH was associated with a 16.4% increase of newborn TSH (95% CI: 3.9%, 30.5%), and each doubling of newborn TSH concentrations was associated with a 10.4% increase in child TSH concentrations at 3 years (95% CI: 0.1%, 21.7%). An interquartile range increase in cord FT4 concentrations was associated with an 11.7% decrease in child TSH concentrations at 3 years (95% CI: −20.2%, −2.3%). Conclusions: We observed relationships between maternal, newborn and child thyroid hormone concentrations in the HOME Study. Our study contributes to understandings of interindividual variability in thyroid function among mother‐child pairs, which may inform future efforts to identify risk factors for thyroid disorders or thyroid‐related health outcomes.